Effect of fatty acids complexed with polyethyleneimine on the flow curves of TiO2 nanoparticle/toluene suspensions*. Issue 3 (1st September 2016) - Iijima, Motoyuki; Kawaharada, Yasuhiro; Tatami, Junichi
Abstract: A series of polyethyleneimine (PEI)–fatty acid complexes using oleic acid (OA), isostearic acid (ISA), and stearic acid (SA) were prepared through a simple process. While PEI was not soluble in toluene, the complex with OA and ISA became soluble when its additive content was greater than 5 mol% based on the ethyleneimine (EI) unit of PEI. PEI–SA had similar solubility in toluene when more than 5 mol% of SA was added; however, the complex precipitated when the additive ratio of SA was increased to 40 mol%. The effect of fatty acid of PEI complexes on their TiO2 nanoparticle adsorption properties and the flow curves of TiO2 nanoparticle/toluene suspension was then studied using PEI complexed with 30 mol% of fatty acids. Surprisingly, while PEI–OA and PEI–ISA complexes effectively adsorbed on TiO2 nanoparticles until saturation, the amount of adsorbed PEI–SA increased continuously. Comparing the flow curves of TiO2 /toluene suspensions under 1.4 mg/m 2 addition of PEI–fatty acid complexes, where PEI–OA and PEI–ISA were under saturated adsorption, it was confirmed that PEI–OA effectively stabilizes TiO2 nanoparticles in toluene without imparting thixotropic properties up to 30 vol%, while the suspensions with PEI–SA and PEI–ISA were solidified at lower volume contents and had high thixotropic properties.